Analisa Postur Kerja untuk Mengukur Risiko Cedera Dengan Metode Cornell Musculoskeletal Discomfort Questionnaires, Rapid Upper Limb Assessment dan Rapid Entire Body Assessment - Wachidatul Bahiyyah, Siti; Isma Putra, Boy (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT. XYZ is a company that focuses on providing construction materials such as ready mix concrete. The workforce is currently in decline due to the reduced prevalence of work behavior. The initial 1 hour produced 100m3 but the realization in the Company only produced 50m3. The purpose of this study was to measure the potential risk of musculoskeletal injury caused by non-ergonomic work postures. The methods used in this study are Cornell Musculoskeletal Discomfort Questionnaires (CMDQ), Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA). This study found a significant relationship between the level of musculoskeletal discomfort obtained in respondents through CMDQ with ergonomic risk factors identified through RULA and REBA analysis. These can include poor body position, repetitive movements, or excessive workload. These findings could help in the development of theories regarding ergonomics and factors related to worker health and well-being.